Nanoscale Construction Biotechnology for Cementitious Materials: A Prospectus - Chen, Xu; Charrier, Marimikel; Srubar, Wil V. (Frontiers in Materials, 2021)
Climate change, infrastructure resilience, and resource recovery from waste have emerged as grand challenges for civil engineers in the 21st century. Wicked problems associated with these global grand challenges are necessitating innovative, multidisciplinary thinking and multiscale, integrated solutions that are spurring the development of a new field—construction biotechnology. While the field of construction biotechnology spans multiple scales, this review highlights the promise and potential of nanoscale (<100 nm) biotechnological applications to civil engineering. While the field of nanotechnology has revolutionized other industries, applications of nanotechnology in civil engineering have remained limited due to techno-economic and environmental barriers. Biological production of functional nanoparticles (NPs), however, offers new economical routes to develop resilient, high-performance cementitious materials while simultaneously addressing critical needs related to wastewater and air-pollution treatment. Recent research has elucidated that biological production of NPs exhibit preferred—and genetically controllable—morphological characteristics that could tailor the structure-property relationships of civil engineering materials. The natural ability as well as the programmability via synthetic biology allow microorganisms to immobilize heavy metals (e.g., Hg, Cr, Zn, Cd, Cu, Ag) and interact with greenhouse gases and volatile organic compounds, therefore affording civil engineers a grand opportunity to treat wastewater and recover rare earth elements, and remove air pollutions. In addition to featuring state-of-the-art research in the field, this review summarizes the opportunities and challenges of nanoscale biotechnology and proposes a roadmap of research for civil engineers of the 21st century.